2006
DOI: 10.1136/aim.24.1.16
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Acupuncture in the Treatment of Temporomandibular Dysfunction – An Audit

Abstract: IntroductionThe term temporomandibular dysfunction (TMD) includes a number of painful conditions involving the masticatory muscles, the temporomandibular joint (TMJ) and the adjacent structures. 1 The aetiology of these pain conditions is not clearly understood but appears to be multifactorial and represents an interaction between physical, functional and psychosocial factors. 1 Acupuncture has been used for treatment of TMD and other musculoskeletal pain conditions, and the results of several studies suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 26 publications
2
13
0
2
Order By: Relevance
“…Other successful reports of TMD treatment with acupuncture are described in the literature, with the descriptions of such adopted treatment approaches [12][13][14][15][16] . In a study 8 , authors have shown the negative impact of oral health on the quality of life of individuals with TMD, a therapeutic problem to be also faced by dentists, being acupuncture one indication for therapeutic approach, where from patients who were submitted in average to 3.4 acupuncture sessions, 85% have benefited with pain intensity decrease of approximately 75% 11 , which is very close to the value of our study. Since pain is a frequent reason to look for the health system 6 , it is up to dentists from the health unit to be able to make the differential diagnosis and so choose the therapy, being acupuncture in public services a useful tool for health promotion actions.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Other successful reports of TMD treatment with acupuncture are described in the literature, with the descriptions of such adopted treatment approaches [12][13][14][15][16] . In a study 8 , authors have shown the negative impact of oral health on the quality of life of individuals with TMD, a therapeutic problem to be also faced by dentists, being acupuncture one indication for therapeutic approach, where from patients who were submitted in average to 3.4 acupuncture sessions, 85% have benefited with pain intensity decrease of approximately 75% 11 , which is very close to the value of our study. Since pain is a frequent reason to look for the health system 6 , it is up to dentists from the health unit to be able to make the differential diagnosis and so choose the therapy, being acupuncture in public services a useful tool for health promotion actions.…”
Section: Discussionsupporting
confidence: 88%
“…Both pain decrease (pain scale from 5.9 to 1.65) and maintenance of this decrease for at least one year after treatment (pain scale 2.45), were observed in this study, which has evaluated results of acupuncture treatment in adult patients with TMD, results which are similar to a different study 11 where the initial pain scale was 7.35 with decrease after acupuncture treatment to 2.67, without, however, evaluating long term results. Our study has evaluated chronic pain, that is, pain which is not characterized as an alert symptom for the occurrence of body injuries, being difficult to control and major cause of disability, being that TMD has major negative impact on the life of people, especially in the items psychological discomfort and disability 8 .…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Studies regarding alternative TMJ therapies include acupuncture (List and Helkimo, 1991;McNeely et al, 2006;Rosted et al, 2006;Smith et al, 2006;Wang et al, 1998), chiropractic (Chinappi and Getzoff, 1995;DeVocht et al, 2003), physical therapy (Cleland and Palmer, 2004;Friedman, 1997;McNeely et al, 2006;Michelotti et al, 2005;Sturdivant and Fricton, 2005), relaxation (Wahlund et al, 2003) and meditation (Masarsky, 1983), all of which report varying degrees of success and suggest further investigation. The most widely studied in this review appears to be acupuncture.…”
Section: Introductionmentioning
confidence: 98%
“…The scale has previously been used in a Danish pilot study concerning the use of acupuncture in dental anxiety. 14 The BAI is a 21-item scale which measures the level of self-reported anxiety. It has demonstrated good convergent and discriminating validity for measuring anxiety levels in clinical and non-clinical populations.…”
Section: Assessment Of Dental Anxietymentioning
confidence: 99%